Is Enceladus' plume tidally controlled? - I. Halevy; S. T. Stewart (Geophysical Research Letters)
Explanations for the plume of gas, water vapor and ice particles jetting from rifts in Enceladus' south polar region include boiling of liquid water and dissociation of clathrate hydrates. In either case, production of the plume may be quasi‐static or tidally controlled, with implications for the interior structure and composition of Enceladus. Previous quantification of the clathrate explanation assumed equilibrium dissociation and cannot be used to simulate a tidally generated plume. We present a non‐equilibrium clathrate dissociation model, which we use to reproduce past observations and predict the plume's properties during upcoming close encounters. The total mass flux and water to gas mass ratio of a tidally generated plume are predicted to be lower than previous measurements. In comparison, for a quasi‐static plume these properties should have values close to previous measurements. This provides an observational means of distinguishing quasi‐static from dynamic processes as the plume's source.